A Potential Link Between Oxidative Stress and Endothelial-to-Mesenchymal Transition in Systemic Sclerosis - Thuan, Duong Thi Bich; Zayed, Hatem; Eid, Ali H.; Abou-Saleh, Haissam; Nasrallah, Gheyath K.; Mangoni, Arduino A.; Pintus, Gianfranco (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc), an autoimmune disease that is associated with a number of genetic and environmental risk factors, is characterized by progressive fibrosis and microvasculature damage in the skin, lungs, heart, digestive system, kidneys, muscles, joints, and nervous system. These abnormalities are associated with altered secretion of growth factor and profibrotic cytokines, such as transforming growth factor-beta (TGF-β), interleukin-4 (IL-4), platelet-derived growth factor (PDGF), and connective-tissue growth factor (CTGF). Among the cellular responses to this proinflammatory environment, the endothelial cells phenotypic conversion into activated myofibroblasts, a process known as endothelial to mesenchymal transition (EndMT), has been postulated. Reactive oxygen species (ROS) might play a key role in SSs-associated fibrosis and vascular damage by mediating and/or activating TGF-β-induced EndMT, a phenomenon that has been observed in other disease models. In this review, we identified and critically appraised published studies investigating associations ROS and EndMT and the presence of EndMT in SSc, highlighting a potential link between oxidative stress and EndMT in this condition.